2015
DOI: 10.1186/s12866-015-0444-2
|View full text |Cite
|
Sign up to set email alerts
|

Importance of sigma factor mutations in increased triclosan resistance in Salmonella Typhimurium

Abstract: BackgroundSalmonella enterica is the second most common foodborne pathogen. The use of biocides is crucial to prevent spread of foodborne pathogens, and it would be devastating for food safety if Salmonella would become resistant to the disinfectants used. Another concern is that exposure to disinfectants might lead to decreased susceptibility to antibiotics.The current study aimed to identify genetic changes causing high level triclosan resistance in S. enterica serovar Typhimurium and evaluate how these affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Expression of acrAB and ompF are controlled by global stress response systems, marRA and soxRS; inserts within marR and soxR (both of which result in derepression of the cognate transcriptional activator genes, which then promote pump expression) were significantly enriched upon triclosan exposure. Inactivation of sigma factors has also been associated previously with triclosan resistance (Gantzhorn et al 2015); in our data, there was significant enrichment of inserts immediately downstream from rpoN ( Fig. 1) but in an antisense orientation in the presence of triclosan, showing that inducible promoters can also identify genes in which repression is beneficial following exposure to a given stress.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Expression of acrAB and ompF are controlled by global stress response systems, marRA and soxRS; inserts within marR and soxR (both of which result in derepression of the cognate transcriptional activator genes, which then promote pump expression) were significantly enriched upon triclosan exposure. Inactivation of sigma factors has also been associated previously with triclosan resistance (Gantzhorn et al 2015); in our data, there was significant enrichment of inserts immediately downstream from rpoN ( Fig. 1) but in an antisense orientation in the presence of triclosan, showing that inducible promoters can also identify genes in which repression is beneficial following exposure to a given stress.…”
Section: Resultssupporting
confidence: 82%
“…Triclosan resistance also appears multifactorial; highly resistant mutants typically have substitutions within FabI that reduce binding efficiency of triclosan, but multidrug efflux pumps, barrier function, changes to fabI expression, core metabolic pathways and sigma factor-controlled stress responses have all been implicated as being involved in triclosan resistance (McMurry et al 1998a;Webber et al 2008a,b;Bailey et al 2009;Gantzhorn et al 2015). A specific link between resistance to fluoroquinolone antibiotics and triclosan, mediated by altered stress responses present in gyrA mutants, has also recently been described (Webber et al 2013).…”
mentioning
confidence: 99%
“…of bacteria. [23][24][25][26][27][28] In some studies, TRI insusceptibility correlates with multiple drug resistance 13,29 ; however, a recent report minimized the impact of TRI exposure on the development of antibiotic resistance in S aureus. 30 Furthermore, it has been observed that bacterialresistant subpopulations to TRI, benzalkonium chloride, and chlorhexidine in clinical isolates may be uncommon.…”
Section: Exposurementioning
confidence: 99%
“…This protein is stress-induced and plays a central role in the control of processes that involve physical interaction of an organism with the environment, as colonization of host surfaces (virulence) or biofilm formation [ 54 ]. Polymorphisms in genes coding for RNA polymerase subunit α ( rpoA, described in mutants selected in QACs) [ 24 , 50 ], and also σ factors ( rpoS and rpoD genes, related to high-level resistance towards TRI) [ 55 ]) were previously reported. Despite other genes coding for RNA polymerase activity ( rpoZ and rpoB ) were shown here to be up-regulated, it corroborates the importance of this protein as a target implicated in intrinsic resistance to biocides [ 23 , 55 ].…”
Section: Discussionmentioning
confidence: 99%